Appropriateness and long-term discontinuation rate of biological therapies in ulcerative colitis. (1st August 2014) - Maillard, Michel H.; Bortolotti, Murielle; Vader, John-Paul; Mottet, Christian; Schoepfer, Alain; Gonvers, Jean-Jacques; Burnand, Bernard; Froehlich, Florian; Michetti, Pierre; Pittet, Valérie
Abstract: Background: Anti-TNFα agents are commonly used for ulcerative colitis (UC) therapy in the event of non-response to conventional strategies or as colon-salvaging therapy. The objectives were to assess the appropriateness of biological therapies for UC patients and to study treatment discontinuation over time, according to appropriateness of treatment, as a measure of outcome. Methods: We selected adult ulcerative colitis patients from the Swiss IBD cohort who had been treated with anti-TNFα agents. Appropriateness of the first-line anti-TNFα treatment was assessed using detailed criteria developed during the European Panel on the Appropriateness of Therapy for UC. Treatment discontinuation as an outcome was assessed for categories of appropriateness. Results: Appropriateness of the first-line biological treatment was determined in 186 UC patients. For 64% of them, this treatment was considered appropriate. During follow-up, 37% of all patients discontinued biological treatment, 17% specifically because of failure. Time-to-failure of treatment was significantly different among patients on an appropriate biological treatment compared to those for whom the treatment was considered not appropriate (p = 0.0007). Discontinuation rate after 2 years was 26% compared to 54% between those two groups. Patients on inappropriate biological treatment were more likely to have severe disease, concomitant steroids and/or immunomodulators. They were also consistently more likely to suffer a failure of efficacy and to stop therapy during follow-up. Conclusion: Appropriateness of first-line anti-TNFα therapy results in a greater likelihood of continuing with the therapy. In situations where biological treatment is uncertain or inappropriate, physicians should consider other options instead of prescribing anti-TNFα agents.